2022
DOI: 10.1136/bmjgh-2022-010294
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence and outcomes of intrapartum-related neonatal encephalopathy in low-income and middle-income countries: a systematic review and meta-analysis

Abstract: AimTo examine the incidence of intrapartum-related neonatal encephalopathy, and neonatal mortality and neurodevelopmental outcomes associated with it in low-income and middle-income countries.MethodsReports were included when neonatal encephalopathy diagnosed clinically within 24 hours of birth in term or near-term infants born after intrapartum hypoxia-ischaemia defined as any of the following: (1) pH≤7.1 or base excess ≤−12 or lactate ≥6, (2) Apgar score ≤5 at 5 or 10 min, (3) continuing resuscitation at 5 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
0
1
0
1
Order By: Relevance
“…Несомненно, такая активность вызвана наибольшей остротой проблемы ГИЭ в этом регионе. Известно, что частота ГИЭ в некоторых странах Азии в несколько раз превосходит частоту ГИЭ, например, в Северной Америке [26,27].…”
Section: региональные особенностиunclassified
“…Несомненно, такая активность вызвана наибольшей остротой проблемы ГИЭ в этом регионе. Известно, что частота ГИЭ в некоторых странах Азии в несколько раз превосходит частоту ГИЭ, например, в Северной Америке [26,27].…”
Section: региональные особенностиunclassified
“…
Research in context
Evidence before this study
We examined the studies included in a recent systematic review on outcomes after hypoxic ischemic encephalopathy from low- and middle-income countries (LMICs) 1 and updated the search on 1 Aug 2023 to identify any additional studies. Total of 5 studies reported neurodevelopmental outcomes after hypoxic ischemic encephalopathy at 18 months or more.
…”
mentioning
confidence: 99%